Expatriates Success Factors (Esf) For Increasing Commitment To Assignment In Arab Markets - HANSON, ROBERT J. (The journal of contemporary issues in business and government, 2021)
Expatriate Success Factors (ESFs) are essential to evaluate expatriate commitment to international assignments. The study aims to identify ESFs that impact expatriate commitment levels;and rank these factors according to their importance. 13 factors were studied, and structured interviews were conducted with 10 experts from different industries. An online survey was distributed to non-Arab expatriates, who were currently working in 22 Arab countries. Valid responses from 5280 expatriates were collected and data was treated using factor loading and statistical analysis.Results indicated that logistical support, compensation, professional development, cultural adjustment, and satisfaction with human resources(HR) procedures are amongst five most important factors impacting expatriates’ commitment to their assignment. This study provides international human resources managers (IHRMs)with areas that must be addressed when locating expatriates abroad. However, further research is needed for non-Arab markets.